Generos Voriinos de Taquinidos chilenos (Diptera: Tachinidae, Voriini) Voriini genera of Chilean Tachinidae - Raúl Cortés P.; Christián R. González A. (Memorias do Instituto Oswaldo Cruz, 1989)
Nine genera and 16 species of Chilean Voriini Tachinid flies are reported in this paper, with a key to differentiate them, a list of recorded species, its geographic distibution within the country and known hosts. The examined examples belong and are deposited at the Collection of Insects of the Instituto de Entomología (UMCE), Santiago. Neochaetoplagia pastranai Blanchard, 1963, from Argentina, and Velardemyia ica Valencia, 1972, from Perú, are reported as present in Chile, while Nothovoria praestans n. gen. & sp., is described as a new monotypic genus.